Relationship between Job Satisfaction and Job Performance among the Engineers in Motorola Penang - Lee, Yen Yng (Universiti malaysia sarawak (UNIMAS), 1998)
This research was conducted in Motorola Penang to identifY the level of job satisfaction and performance and the correlation of job satisfaction and job performance among 50 engineers from two departments (AMT and R&D). Specifically, the difference between selected demographic characteristic (departments, age, education and tenure) and job satisfaction; and the relationship between factors of job satisfaction (the work itself, pay, promotion, supervisor, co-workers) and job performance were examined. The standard Job Descriptive Index (JDI) and behavioural checklist were used to measure job satisfaction and job performance. Descriptive statistic, T-test, ANOVA, Pearson Correlation and Multiple Regression were applied to test the hypotheses of this study. Overall, the engineers showed a moderate job satisfaction and a relatively high job performance. There is no significant difference between selected demographic characteristic and job satisfaction. The engineers reported the highest satisfaction towards their supervisor, followed by the work itself, co-workers, promotion and lastly the pay. Meanwhile, there is a significant and moderate relationship between overall job satisfaction and job performance (r = .422). In addition, satisfaction on the work itself and promotion were found to have significant relationship with job performance, where promotion is the most dominant factor to job performance while the work itself takes on the second place. These two factors contributed approximately 30 percent to job performance. The implication of these findings is that the organization should make improvement upon the pay system and promotion policy to boost the engineers' job satisfaction. On the other hand, in order to retain a high level of job performance among the engineers, the organization should ensure that the work itself and promotion factor are able to meet the engineers' needs from the aspect of achievement, challenge, growth, responsibility, recognition and self-actualization.